APPLICATION OF LEARNING CYCLE MODEL (5E) LEARNING WITH CHART VARIATION TOWARDSTUDENTSâ CREATIVITY - -, Suciati; Vincentrisia, A.; -, Ismiyatin (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2015)
This study aims to determine the differences in the application of the model LC (5E) with a technique variation (interrelationship diagram / ID and affinity diagrams / AD) of two classes of different school (XIPA-8 class of SMAN 3 Surakarta and class XIPA-6 of SMAN 3 Boyolali), toward the increase of studentsâ creativity. This research is a qualitative descriptive study. The results of this study, we can conclude that the application of the model LC (5E) with a technique variation at two schools can improve students creativity despite different levels of improvement.